The Influence of Digital Learning Media in Office Automation II Course on Student Learning Outcomes - Muh. Darwis; Indra Indra; Sitti Hardiyanti Arhas (Jurnal Ad'ministrare, 2023)
The development of learning media continues to experience improvements and various variations, and until now it has been digitally integrated following technological developments so that indirectly it also requires teaching staff and students to adapt to the current advances in science and technology. The use of appropriate learning media can trigger students' mastery of material so as to provide optimal results for increasing learning outcomes and being able to implement these values into everyday life. This study aims to determine the description of digital learning media, learning outcomes and the influence of digital learning media on student learning outcomes of the Office Administration Education Study Program. This research is quantitative bivariate research that shows a causal relationship. The sample in this study was 47 people with proportional random sampling technique. Data collection techniques used are observation, questionnaires, interviews, and documentation. The data analysis technique used is descriptive and inferential statistical analysis. The results of the study show that digital learning media is in a good category, and student learning outcomes are in a very high category. Based on the results of the product moment correlation test, the relationship between variables is moderate. The results of simple linear regression analysis show that there is a positive and significant influence of digital learning media on the learning outcomes of students of the Office Administration Education Study Program